Why simulate a sample of recycled wood? - Bouslamti, A.; Irle, M.A.; Belloncle, C.; Salvador, V.; Bondu, M.; Hulot, S.; Caron, B. (Maderas. Ciencia y Tecnología, 2025)
Wood products follow the same cycle as other materials: manufacture, use and disposal. For certain applications, chemical additives are added to wood to increase its durability against biological and physical attack. At the end of life, waste wood is chipped or crushed before being recovered as raw material for new products or as fuel for energy. In recycled wood, there is the potential that some wood particles are contaminated by hazardous substances, such as organic or heavy metal preservatives. Therefore there is a need for a quality control method of assessing recovered wood that is on the one hand sufficiently precise and on the other not too expensive to preclude the use of recycling wood in to new products. This paper covers some preliminary research that is part of a large study that aims to develop a robust analytical method for recovered wood. However the extreme variability of recovered wood makes it difficult to develop such protocols on real recovered wood samples. Consequently, model chip piles with known contamination levels were created to simulate real world recovered wood samples.